Dampak Game Online terhadap Pola Belajar Anak: Studi di Desa Ujung Tanjung III Kabupaten Lebong - Teddy Aprilianto (UIN Fatmawati Sukarno Bengkulu, Indonesia, 2020)
Each child has diverse learning patterns. The foregoing is definitely influenced by various factors, including their interactions with peers. This is also felt by children in Ujung Tanjung III village in Lebong Regency. Peer association changes their learning intensity into an interest in playing online games. Anchored in this issue, this study sought to find out the answers as regards the impact of online games on children's learning patterns in that village by using a qualitative approach. The data of this study were collected through observation and interviews, and it was concluded that the habits of online gaming had a negative impact on children's learning patterns at home. The related indicators extended to that the children did not have a priority scale in carrying out their daily activities including learning at home; they tended to act in dissociate ways; and they were lazy to learn.